2003
DOI: 10.2320/matertrans.44.775
|View full text |Cite
|
Sign up to set email alerts
|

Materials Processing for Structural Stability in a ZK60 Magnesium Alloy

Abstract: The materials processing, consisted of a four step process of solution treatment, pre-strain, overaging and hot working, was developed for attaining structural stability at high temperatures in a commercial Mg-Zn-Zr alloy, ZK60. The grain size of the material processed by this schedule was refined to 2.5 mm, and the material behaved in a superplastic manner at 548 K and at a strain rate of 1 Â 10 À2 s À1 owing to the grain size stability at this temperature. From the analysis of the chemical composition of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…These precipitates are MgM (M = Zn,Zr) intermetallics, according to energy dispersive X-ray spectroscopy characterization by Watanabe et al [25] Figure 5 shows the dissociation of a dislocation. The split width is narrow, suggesting a relatively high stacking fault energy (SFE).…”
Section: Results and Analysesmentioning
confidence: 99%
“…These precipitates are MgM (M = Zn,Zr) intermetallics, according to energy dispersive X-ray spectroscopy characterization by Watanabe et al [25] Figure 5 shows the dissociation of a dislocation. The split width is narrow, suggesting a relatively high stacking fault energy (SFE).…”
Section: Results and Analysesmentioning
confidence: 99%
“…The rods growing along the [0001] direction are the Pi' phase, and the Pi' phase have the size of 620 ±150 nm in length and 30 ± 10 nm in diameter. The plates are the P2' phase [6], and they have the size of 30 ± 10 nm in thickness and 10 ± 5 nm in diameter. Figure 3 The fii' and P2' phases observed in the as-cast sample are much coarser than those observed in the heat treated sample [8], However, EDS elemental maps clearly confirms the presence of the Mg(Zn,Zr) phase.…”
Section: Resultsmentioning
confidence: 99%
“…Zr-enriched cores formed during melting have been believed to provide nucleation sites for the magnesium grains leading to the grain refinement [2][3][4][5], Recent studies have reported some overlooked roles of Zr in the Mg-Zn based alloys [6][7][8][9][10], Bhattacharjee et al reported that Mg(Zn,Zr) precipitates are formed in a ZK60 cast alloy subjected to a heat treatment at 350°C [8], The structure of the Mg(Zn,Zr) precipitates were identical to MgZm type phases of Pi' and P2' phases, which are typically observed in the Mg-6Zn (Z6) alloy subjected to aging. Since the J31' and P2' phases in the aged Mg-6Zn (Z6) alloy are dissolved by heat treatment at 350 °C, they concluded that Zr stabilized the Pi' and P2' precipitates at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Rod shaped precipitates were formed, and the similar shaped precipitates have been observed by aging process. [21][22][23] Similar aging conditions occurred in the extrusion container before extrusion. Therefore, it is assumed that the spherical shaped precipitates were formed during the extrusion process in comparison with Fig.…”
Section: Initial Microstructuresmentioning
confidence: 90%